Pengaruh Pendidikan Kesehatan Pranikah Terhadap Pengetahuan dan Sikap Calon Pengantin di Lubuk Begalung Padang Tahun 2017 - Dewi Susanti; Alsri Windra Doni; Yefrida Rustam (Jurnal Sehat Mandiri, 2018)
Divorce rates in Indonesia in the last five years show a significant number where Indonesia ranks fifth with 276,791 cases. The purpose of this study was to determine the effect of premarital health education on the knowledge and attitudes of brides in Lubuk Begalung Subdistrict, Padang City in 2017. The type of research was quasy experiment with pretest-posttest design. The study was conducted in KUA Lubuk Begalung District in April-June2017. Population in this research bride and groom who came to KUA Lubuk Begalung District during the research period were 19 couples taken by purposive sampling. Data collection used questionnaires given before and after health education. Data analysis was done by univariate and bivariate using Wilcoxon statistical test with computer. Results Research on 38 prospective brides showed that 31.6% of respondents were low knowledge before premarital education and 97.4% were highly knowledgeable after premarital education, 76.3% were negative before premarital education. There is the influence of premarital education on the knowledge and attitudes of the bride and groom (p value 0.001 and 0.013) Conclusion there is the effect of premarital health education on the knowledge and attitudes of brides in the District of Lubuk Begalung Padang in 2017